Weakening of the AMOC and strengthening of Labrador Sea deep convection in response to external freshwater forcing - Xinyue Wei; Rong Zhang (Nature Communications)
Abstract The Atlantic Meridional Overturning Circulation (AMOC) is a key player in climate. Here, we employ an ensemble of water hosing experiments to examine mechanisms of AMOC weakening and its subsequent impact on the Labrador Sea open-ocean deep convection. The subpolar AMOC decline in response to the external freshwater flux released over the southern Nordic Sea is dominated by that across the eastern subpolar North Atlantic, and the largest subpolar AMOC decline is at the relatively dense level around $${σ }_{0}=27.84\,{{{\rm{kg}}}}\,{{{\rm{m}}}}^{-3}$$ σ 0 = 27.84 kg m − 3 . The AMOC decline is associated with subsurface cooling in the subpolar North Atlantic and the decline in the deep ocean west–east density contrast across the subpolar basin. Contrary to previous studies showing that the AMOC decline is caused by subsurface warming through the shutdown of the Labrador Sea open-ocean deep convection, our results reveal a different response, i.e., a strengthening of the Labrador Sea open-ocean deep convection, which is not a cause of the AMOC decline. The strengthening of the Labrador Sea open-ocean deep convection is mainly due to the relatively stronger freshening in the deep Labrador Sea associated with the freshening/weakening of the Iceland-Scotland Overflow, and thus reduced vertical stratification in the central Labrador Sea.